Comedy acting for theatre the art and craft of performing in comedies - Homan, Sidney 1938-; Rhinehart, Brian (Methuen Drama, 2018)
"Rooted in performance and performance criticism Comedy Acting for Theatre is a textbook which offers a detailed examination of how comedy works, along with advice for the actor sending a comic message, allowing them to better understand the communication of comedy from the point of view of both the performer and the audience. Applying the twin perspectives of theory and performance, the authors analyse a variety of plays, both modern and classic, from writers including Harold Pinter, Tom Stoppard, Christopher Durang, Michael Frayn, among others, as well as an extensive exploration of acting in Shakespeare's comedies. Analysing why we laugh and what we laugh at, and describing how performers can elicit this response from their audience, Comedy Acting for Theatre: The Art and Craft of Performing in Comedies is a detailed and essential handbook for actors seeking to put in memorable - and hilarious - performances"--Provided by publisher.